Fintech Lending Readiness, Borrower Trust, and Credit Access among Vietnamese SMEs: The Mediating Role of Information Transparency - Nguyễn Thị Minh Anh Nguyễn Thị Minh Anh; Trần Văn Nam Trần Văn Nam; Kanya Rattanapong Kanya Rattanapong (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2025)
Fintech lending platforms have expanded rapidly across Southeast Asia, promising faster credit decisions and broader access for small and medium-sized enterprises (SMEs) that struggle with conventional collateral-based banking. Even so, many SMEs remain hesitant to rely on digital lenders, and platform usage frequently fails to translate into reliable credit access when borrowers cannot demonstrate credible information, predictable repayment capacity, or procedural transparency. This study examines how fintech lending readiness influences perceived credit access among Vietnamese SMEs through borrower trust and information transparency. Drawing on signaling theory, technology trust perspectives, and information asymmetry logic, the model treats readiness as an operational capability that combines digital preparedness, documentation discipline, and procedural familiarity. Survey data were collected from 418 Vietnamese SMEs across manufacturing, services, and agri-business sectors. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test direct effects and parallel mediation. The results indicate that fintech lending readiness relates positively to perceived credit access, with borrower trust and information transparency operating as complementary mediators. The findings suggest that digital credit inclusion depends not only on platform availability but also on the borrower’s capacity to present verifiable information and to interpret lending processes confidently. Policy implications emphasize integrating SME digital bookkeeping support with platform governance standards that improve explainability, dispute handling, and fairness perceptions.